2019
DOI: 10.1007/s10549-019-05168-1
|View full text |Cite
|
Sign up to set email alerts
|

Germline TP53 mutation spectrum in Sudanese premenopausal breast cancer patients: correlations with reproductive factors

Abstract: Purpose The role of non-genetic factors as modifiers of TP53 -related hereditary breast cancer (BC) risk is debated. In this regard, little is known about the impact of germline TP53 mutations on BC in sub-Saharan Africa, where the disease often presents in non-contraceptive multiparous premenopausal women with extended history of breastfeeding. Herein, we report the germline TP53 mutations found in a series of 92 Sud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 27 publications
1
1
1
Order By: Relevance
“…Armitage trend test. These results are in line with those reported elsewhere in Africa where, whatever the menopausal status, no association was reported between polymorphism at rs1042522 of TP53 and the risk of BC development[19] [48]. However, it is important to point out that the allele frequencies were not in HWE at this locus when the entire population was analyzed.…”
supporting
confidence: 91%
See 1 more Smart Citation
“…Armitage trend test. These results are in line with those reported elsewhere in Africa where, whatever the menopausal status, no association was reported between polymorphism at rs1042522 of TP53 and the risk of BC development[19] [48]. However, it is important to point out that the allele frequencies were not in HWE at this locus when the entire population was analyzed.…”
supporting
confidence: 91%
“…Although the CG genotype of TP53 has not been implicated in premenopausal BC susceptibility [48], results (adjusted p-value of 0.002 and an OR of 0.39) of our study revealed its association with a reduced risk of developing BC in premenopausal women. These results contrast those of Cherdyntseva et al [61] reporting that CG genotype seemed to increase the risk of BC in premenopausal Caucasian patients.…”
Section: Discussioncontrasting
confidence: 71%
“…A mutation in the TP53 gene often accompanies BRCA mutations in breast and ovarian cancers, making the mutations in these DNA repair genes relevant in therapeutic interventions ( 90 , 91 ). The publications on TP53 mutation have focused on its expression in breast cancer and the contribution of its polymorphism, particularly codon 72 to breast cancer ( 28 , 31 , 33 , 36 , 92 94 ), as well as to its interaction with MDM2 344T>A polymorphism in response to chemotherapy of breast cancer in Tunisia ( 95 ). Other DNA repair genes that have been studied in Africa include XRCC1 and XPD in Egypt ( 96 , 97 ).…”
Section: Resultsmentioning
confidence: 99%
“…Similar type of epidemiological studies reported from India for those SNPs and their association with cancer development (Lakshmi et al, 2012;Saikia et al, 2014;Khan et al, 2020) whereas other objected for their association with carcinogenesis in different ethnic population (Pillai and Nasir 2016;Bansal et al, 2016). Various investigations reported some associations of the studied genes with breast cancer development (Ayobi et al, 2018;Diakite et al, 2021) whereas others suggested no association between the polymorphisms either of p21 or p53 genes and the breast carcinogenesis (Habyarimana et al, 2018;Aceto et al, 2019;Zhao et al, 2022). The major attention of this study was to identify the polymorphisms in p53 gene in rural women of Maharashtra and demonstration of their association with risk of BC in studied population.…”
Section: Discussionmentioning
confidence: 86%